Using Couplings to Suppress Chaos and Produce a Population Stabilisation Strategy - Lopes, Luís M.; Grácio, Clara; Fernandes, Sara; Fournier-Prunaret, Danièle (Regular and Chaotic Dynamics, Pleiades Publishing, Ltd., 2023)
The chaotic behaviour of dynamical systems can be suppressed if we couple them in some way. In order to do that, the coupling strengths must assume particular values. We illustrate it for the situation that leads to a fixed point behaviour, using two types of couplings corresponding either to a diﬀusive interaction or a migrative one. For both of them, we present strategies that easily calculate coupling strengths that suppress the chaotic behaviour. We analyse the particular situation of these couplings that consists in a symmetric one and we propose a strategy that provides the suppression of the chaotic evolution of a population.
Keywords: suppression of chaos; diﬀusive coupling; migrative coupling; symmetric coupling; stabilisation of a population